A PDGFRα-driven mouse model of glioblastoma reveals a stathmin1-mediated mechanism of sensitivity to vinblastine - Hyun Jung Jun (Nature Portfolio, 2018)
Amplification of PDGFRα is a common alteration in glioblastoma. In this study, the authors develop a genetically engineered mouse model of GBM based on autocrine, chronic stimulation of overexpressed PDGFR and discover Stathmin1 as an important PDGFRα regulated-protein involved in the response to vinstabline.